Breast Cancer Nodes Detection Using Ultrasonic Microscale Subarrayed MIMO RADAR. (15th September 2014) - Taparugssanagorn, Attaphongse; Siwamogsatham, Siwaruk; Pomalaza-Ráez, Carlos
Abstract : This paper proposes the use of ultrasonic microscale subarrayed MIMO RADARs to estimate the position of breast cancer nodes. The transmit and receive antenna arrays are divided into subarrays. In order to increase the signal diversity each subarray is assigned a different waveform from an orthogonal set. High-frequency ultrasonic transducers are used since a breast is considered to be a superficial structure. Closed form expressions for the optimal Neyman-Pearson detector are derived. The combination of the waveform diversity present in the subarrayed deployment and traditional phased-array RADAR techniques provides promising results.